Pengembangan Buku Cerita Ramayana Berbahasa Jawa sebagai Penunjang Pembelajaran Sastra Wayang Bagi Siswa Tunagrahita SMPLB di Semarang - Kirom, Dina Ashlikhatul; Mujimin, Mujimin; Widodo, Widodo (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Ramayana is a story about the Javanese puppet there in Kurikulum 2013 for Junior High School. Extraordinary Junior High School (SMPLB), specifically mental retardation, used that curriculum. The teacher of SMPLB is a classroom teacher there was find it difficult using Ramayana’s story for the lesson. Lack of teaching materials and student interest to learn Ramayana’s story make Javanese Ramayana storybook worthy to be developed. Based on the questionnaire, this Javanese Ramayana storybook is needed by teachers and students. Then generated the storybook